MON-524 Prospective Evaluation of Patients with Encapsulated Classical Variant of Papillary Thyroid Cancer and Noninvasive Follicular Thyroid Neoplasm with Papillary-Like Nuclear Features (NIFTP): Have They A Similar Prognosis? - Giani, Carlotta (J Endocr Soc, 2020)
Background: Our previous retrospective study demonstrated that the absence of tumor capsule or, if present, its invasion were independent risk factors for the persistence of the disease (OR 6.75, CI 1.97-23.08 and OR 7.89, CI 1.78-34.94, respectively) in papillary thyroid cancer (PTC). This data was confirmed also analyzing separately the most frequent PTC variants [follicular variant (FVPTC) and classical variant (CVPTC)]. Moreover, we demonstrated that the absence of tumor capsule was significantly more frequent in FVPTC BRAF V600E mutated than FVPTC wild-type for BRAF gene or with rare-BRAF mutations (e.g., BRAF K601E, BRAF V600_K601delinsE). These data confirmed the importance of the integrity of the tumor capsule in FVPTC which led in 2016 to the definition of a new thyroid neoplasm entity named NIFTP. According to these retrospective data, we have assumed that the integrity of the tumor capsule in CVPTC could have a prognostic role similar to that confirmed in the NIFTP group. Methods: we have prospectively collected data of patients (pts) underwent total thyroidectomy or lobectomy for encapsulated-CVPTC (E-CVPTC) or NIFTP. In both cases the tumor was accurately analyzed by the pathologists according to the criteria used for the NIFTP (in particular with one capsule sample every 1 mm). All pts performed at least one clinical control and neck US within 6 months from surgery. Results: From January 2018 to June 2019, 144 E-CVPTC and 177 NIFTP were prospectively collected. 83/144 (57.6%) E-CVPTC and 106/177 (59.8%) NIFTP cases were included. The others were excluded due to the presence of other thyroid tumors associated in the same gland. No differences in epidemiological and pathological features were found between E-CVPTC and NIFTP except for the tumor size, significantly bigger in NIFTP than E-CVPTC [22±16mm (2-68) vs 8±11mm (1-80), p<0.00]. A significantly higher rate of NIFTP’ pts underwent lobectomy respect to E-CVPTC pts (34%vs14.5%, p=0.02). After a mean of 9 months of follow-up all pts had an excellent response according to ATA guidelines. Conclusions: These prospective data demonstrated that NIFTP and E-CVPTC have a similar clinical behavior in a short-term follow-up, thus suggesting that the presence of an intact tumor capsule is predictive of a good outcome. A longer follow up is needed to confirm these initial interesting findings.